Risk-Benefit Assessment of Feed Additives in the One Health Perspective - Mantovani, Alberto; Aquilina, Gabriele; Cubadda, Francesco; Marcon, Francesca (Frontiers in Nutrition, 2022)
Safety and sustainability of animal feeds is a pillar of the safety of the entire food chain. Feed additive assessment incorporates consumer safety as well as animal health and welfare, which, in turn, can affect productivity and hence food security. The safety of feed users and the environment are other important components of the assessment process, which, therefore builds on a One Health perspective. In several instances the assessment entails a balanced assessment of benefits and risks for humans, animals and/or the environment. Three case studies are selected to discuss issues for a consistent framework on Risk-Benefit Assessment (RBA) of feed additives, based on EFSA opinions and literature: a) Supplementation of feeds with trace elements with recognized human toxicity (cobalt, iodine) - RBA question: can use levels, hence human exposure, be reduced without increasing the risk of deficiency in animals?; b) Aflatoxin binders in dairy animals - RBA question: can the use reduce the risk for human health due to aflatoxin M1, without unexpected adverse effects for animals or humans?; c) Use of formaldehyde as preservative in feedstuffs to prevent microbial contamination - RBA question: is the reduction of microbiological risks outweighed by risks for the consumers, farmed animals or the workers?